TREATMENT OF UNDILUTED HUMAN WASTE BY THE ACTIVATED SLUDGE PROCESS - Baumgartner, D. J.; Walters, C. F. (1964)
A laboratory activated sludge system was operated to confirm field investigations which indicated that a 423 gallon recirculating activated sludge system could adequately treat the undiluted human wastes from 10 men for at least six months and provide an effluent acceptable for use as a flushing fluid. In addition, the level and the effects of overloading were noted. The effect of high pH on odor production was observed, and the importance of pH control between 6 and 7 was demonstrated. The feed COD of 44,000 mg/1 (BOD = 21,000 mg/ 1) was reduced by about 90 per cent and the estimated water savings for toilet flushing was estimated at greater than 90 per cent. Prepared under Cross Service Agreement CSA 61-1.